Examining the experience of childbirth and its predictors among women who have recently given birth - Faeze Khalife‐Ghaderi; Leila Amiri‐Farahani; Shima Haghani; Syedeh Batool Hasanpoor‐Azghady (Wiley, 2021)
Abstract Aims The aim of this study is to examine the experience of childbirth and its predictors among women who have recently given birth. Design This is a cross‐sectional study. Methods This study was conducted on 225 women at 22 Bahman Hospital in Khaf City, Iran. The samples were selected by the continuous sampling method from August to November 2018. Data were collected by demographic questionnaire, fertility information, pregnancy experience scale, satisfaction from birth environment inventory and the childbirth experience questionnaire. Results The mean score of childbirth experience was 55.73. According to the regression model, the husband's education, receiving regular care during pregnancy, the person giving birth, presence of a companion, receiving spinal anaesthesia, perineal conditions, being uplifted and hassled about the pregnancy and satisfaction with the birth environment were the predictors of childbirth experience. The regression model showed 39.8% of the change in outcome variable was predicted by independent variables.